Escrita masculina/personagens femininas: os contos de Rinaldo de Fernandes. - Gama, Gloria Maria Oliveira (2012)
The present research aims at analyzing short stories by the contemporary writer Rinaldo de Fernandes, focusing on the form with which this writer portrays his female characters in his short narrative. The corpus of analysis is composed of four of his short stories. In three of them, we can meet female protagonists who are, to our view, convincing and true-to-life. On the fourth short story, we have a male protagonist, whose analysis will both contrast and complement the proposed debate on authorship and female character. The premise is to demonstrate that the portrayal of women in literature can be comfortably done by a male writer, as, throughout the presented considerations, we intend to disengage the concept of authorship from any notion of typified writing as related to the sex of the one who has produced the text. In order to reach our goals, we shall refer to some theorists of the feminist literary criticism. The purpose is to relativize their assertions other than (re)affirm them. Besides that, other theorists shall help us to widen the debate round such issues as gender, identity (as proposed by cultural studies), sex in writing, as well as the definitions of short story as textual genre. Departing from these theoretical and critic viewpoints, we propose to discuss the selected short stories.